Integration of Al-Qur’an Values ​​in the Pancasila Student Profile Strengthening Project (P5) - Sakinah, Mufidah; Khozin; Muhammad Yusuf (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to analyze the integration of Al-Qur’an values ​​in the Pancasila Student Profile Strengthening Project (P5), especially the theme of Local Wisdom. This research uses a qualitative approach, with a case study type. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data display, and drawing conclusions as well as checking the validity of the data using triangulation. The results of this research show that the application of Pancasila Student Profile Strengthening Project (P5) through understanding the values of the Al-Qur’an can develop the quality of Islamic Religious Education learning, because it can unite the values of Pancasila with the values contained in the Al-Qur’an. The relationship between the values in the Al-Qur’an is also an important point to unite the theme of local wisdom with the values in the Al-Qur’an, namely the value of diversity in Surah Al-Hujurat verse 13. The concept of the diversity theme discusses regarding cultural and religious tolerance, respecting values, traditions and cultural heritage, appreciating and respecting differences and establishing harmony among religious communities, these are the main points in building Pancasila values in the realm of Indonesian unity.